SISTEM INFORMASI GEOGRAFIS WISATA KULINER BERBASIS ANDROID - Tantry Wahyuni; II SOPIANDI (INFOTECH journal, 2020)
Information and Communication Technology has made the Geographic Information System (GIS)develop significantly. The development of culinary tourism locations in the Majalengka area more and more, this causes culinary connoisseurs, especially those from outside the Majalengka area, it isdifficult to find culinary tourism locations. The purpose of this study is to display the androidgeographic information system in Majalengka Regency and Implement an android-based culinary tourism application so that it makes it easier to find locations. The method used in making geographic information systems based on android culinary tourism is to use the waterfall method, where this method begins with a system analysis, system design, implementation, testing and Maintenance. At the coding stage using Java Scrpit as a programming language, PHP 5.6.38 as a web server, MySQL5.0.21 as a database, and Android Studio as an application in making adroid. Testing is the testing phase using a blackbox. The results of the study will be an application that can be installed on android with a minimum Android Lollipop 5.0 Smartphone where there will be a restaurant name, menu, location and route that can be displayed on google maps.Keywords: Geographic Information Systems, Culinary Tourism, Waterfall, and Android.